Income convergence among U.S. states: cross‐sectional and time series evidence. (20th August 2013) - Heckelman, Jac C.
Abstract: We perform convergence tests on the U.S. states for per capita income from 1930 to 2009. Cross‐sectional tests support overall σ‐convergence and β‐convergence but may not hold true for the last three decades. Time series tests suggest that about half of the states exhibit stochastic convergence and of these all are also β‐converging. Probit regressions reveal that the likelihood a state is converging is a function of changing capital to labour ratios, the size of the agricultural sector, and levels of taxation and tax revenue. Regional disparities in convergence remain among the southern and midwestern states. Abstract : Convergence des niveaux de revenus entre les états américains : résultats á partir de donnés transversales et de séries chronologiques . On présente des tests de convergence des revenus per capita des états américains entre 1930 et 2009. Les tests transversaux supportent l'hypothèse de convergence de type σ et de type β, mais pourraient ne pas tenir pour les trois dernières décennies. Les tests utilisant les séries chronologiques suggèrent que la moitié des états montrent une convergence stochastique, et que de ceux‐ci tous supportent l'hypothèse de convergence de type β. Des régressions par la méthode probit révèlent que la vraisemblance qu'un état converge dépend des rapports capital/travail changeants, de la taille du secteur agricole, et des niveaux de taxation et de rentrées fiscales. Des disparités régionales dans la convergence demeurent entre les états du sud et du midwest.